1994
DOI: 10.1042/bj3040235
|View full text |Cite
|
Sign up to set email alerts
|

Function of streptokinase fragments in plasminogen activation

Abstract: Several peptide fragments of streptokinase (SK) were prepared by incubating SK with immobilized human plasmin (hPlm) and purified by h.p.l.c. with a reverse-phase phenyl column. The N-terminal sequences, amino acid compositions and molecular masses of these peptide fragments were determined. The SK peptide fragment of 36 kDa consisting of Ser60-Lys387 (SK-p), was the only peptide fragment that could be tightly bound to immobilized hPlm. Another three large SK peptide fragments, SK-m, SK-n and SK-o, with molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
76
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 33 publications
12
76
2
Order By: Relevance
“…SK complex and to bind a substrate Plg molecule, yet possesses a reduced catalytic rate constant for Plg activation (Lin et al, 1996). It appears therefore that whereas SK domain B mediates an interaction with Plg within the activator complex (this study; Shi et al, 1994;Young et al, 1995;Parrado et al, 1996), the function of inducing the active SK.Plg complex to proteolyse specifically the activation peptide bond of substrate Plg molecules appears to reside within domain C (Young et al, 1995).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…SK complex and to bind a substrate Plg molecule, yet possesses a reduced catalytic rate constant for Plg activation (Lin et al, 1996). It appears therefore that whereas SK domain B mediates an interaction with Plg within the activator complex (this study; Shi et al, 1994;Young et al, 1995;Parrado et al, 1996), the function of inducing the active SK.Plg complex to proteolyse specifically the activation peptide bond of substrate Plg molecules appears to reside within domain C (Young et al, 1995).…”
Section: Discussionmentioning
confidence: 76%
“…However, this interaction alone is incapable of engendering Plg activation. The remaining Plg-binding determinants within SK have been proposed to reside within an N-terminal region (residues 1-90 approximately) (Shi et al, 1994;Rodriguez et al, 1995b;Young et al, 1995) contained within the N-terminal domain A (residues 1-145 approximately) (Conejero-Lara et al, 1996;Parrddo et al, 1996). Additionally, the presence of domain C (residues 290-380 approximately) appears to be essential for active site formation in the SK.Plg complex and subsequently for its Plg activator activity (Reed et al, 1995;Young et al, 1995;Parrado et al, 1996).…”
mentioning
confidence: 99%
“…Several previous studies have indicated the importance of approximately the first 60 residues at the N terminus of SK in the regulation of its Plg activator activity (Siefring & Castellino, 1976;Shi et al, 1994;Young et al, 1995;Parrado et al, 1996). These N-terminal peptides (similar to fragment AI) remain noncovalently bound to the rest of the SK chain in proteolytic preparations (Siefring & Castellino, 1976;Misselwitz et al, 1992;Parrado et al, 1996) and are capable of producing a large increase in the activity of other SK fragments (Shi et al, 1994;Parrado et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These N-terminal peptides (similar to fragment AI) remain noncovalently bound to the rest of the SK chain in proteolytic preparations (Siefring & Castellino, 1976;Misselwitz et al, 1992;Parrado et al, 1996) and are capable of producing a large increase in the activity of other SK fragments (Shi et al, 1994;Parrado et al, 1996). Isolated fragment A1 has been described as being mainly unstructured at neutral pH, under conditions where it was capable of potentiating the activator activity of fragment A2-B-C up to 100-fold (Parrado et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation